2006
DOI: 10.1007/s10548-006-0013-y
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Modifications During Visuomotor Association Learning Assessed by Electric Brain Tomography

Abstract: Summary: In everyday life specific situations need specific reactions. Through repetitive practice, such stimulus-response associations can be learned and performed automatically. The aim of the present EEG study was the illustration of learning dependent modifications in neuronal pathways during short-term practice of visuomotor associations. Participants performed a visuomotor association task including four visual stimuli, which should be associated with four keys, learned by trial and error. We assumed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 64 publications
(60 reference statements)
0
10
1
1
Order By: Relevance
“…It should be stressed that the results of the current experiment support a role of the premotor cortex in procedural motor memory consolidation, but that this does not exclude the involvement of other areas, such as supplementary motor area and parietal cortices, which are also involved in motor learning and represent a memoryrelevant network (Praeg et al 2006). Moreover, the results of the present study do not allow one to make assumptions about the relative contribution of these different areas to consolidation.…”
Section: Discussioncontrasting
confidence: 84%
“…It should be stressed that the results of the current experiment support a role of the premotor cortex in procedural motor memory consolidation, but that this does not exclude the involvement of other areas, such as supplementary motor area and parietal cortices, which are also involved in motor learning and represent a memoryrelevant network (Praeg et al 2006). Moreover, the results of the present study do not allow one to make assumptions about the relative contribution of these different areas to consolidation.…”
Section: Discussioncontrasting
confidence: 84%
“…Second, most importantly for this experiment is that the lower alpha band reflects general task demands and attentional processes. We anticipated that these psychological processes (general task demands and attention) will be involved in visuomotor learning as studied here (Praeg et al 2005;Praeg et al 2006;Toni et al 2001). In addition, recent combined EEG and fMRI studies have elegantly shown that the alpha band negatively correlates with the BOLD response in parietal and frontal brain regions that are known to be involved in visuomotor control processes (Laufs et al 2006a;Laufs et al 2006b).…”
Section: Electrophysiological Datamentioning
confidence: 99%
“…More specifically, the posterior parietal cortex is usually involved in various cognitive tasks, as for example re-direction of attention (Rushworth et al 2003), visuo-spatial behaviour (Babiloni et al 2006;Thayer and Johnson 2006) or integration of visuo-motor information (Berndt et al 2002;Holz et al 2008;MacKay and Mendonça 1995;Praeg et al 2006). It is principally involved in planning and execution of actions and it is considered as part of the visual dorsal stream for action (Milner and Goodale 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the existence of complex patterns of activation during attention and/or visuo-spatial and visuo-motor tasks have been reported (Berndt et al 2002;Holz et al 2008;Praeg et al 2006;Thayer and Johnson 2006), indicating the involvement of both parietal and frontal areas but not clarifying the involvement and amount of functional connections among them (Berndt et al 2002;Holz et al 2008;Praeg et al 2006).…”
Section: Introductionmentioning
confidence: 99%